Changes in Restrictive Spirometric Pattern and Pulmonary Function Before and After the COVID-19 Pandemic Among Korean Adults: A Nationwide Cross-Sectional Study - Taner Akbulut; Vedat Çinar; Do-Youn Lee (Journal of Clinical Medicine, 2026)
Background/Objectives: A restrictive spirometric pattern (RSP), characterized by reduced forced vital capacity (FVC) with a preserved FEV1/FVC ratio, has been associated with adverse health outcomes and metabolic disorders. This study investigated differences in the prevalence of RSP and pulmonary function between 2019 and 2024 among Korean adults. Methods: This cross-sectional study analyzed data from the 2019 and 2024 Korea National Health and Nutrition Examination Survey. A total of 4856 adults aged ≥40 years without chronic obstructive pulmonary disease were included. RSP was defined as FVC < 80% predicted among participants with an FEV1/FVC ratio ≥ 0.70. Pulmonary function and RSP prevalence were compared between survey years using complex sample analyses. Multivariable logistic regression was performed to examine the association between the post-pandemic period and RSP. Results: The prevalence of RSP increased significantly from 2.31% in 2019 to 3.58% in 2024 (p = 0.025). FVC, FEV1, and FVC percent predicted significantly decreased after the COVID-19 pandemic (all p < 0.001), whereas the FEV1/FVC ratio (p = 0.166) and peak expiratory flow (p = 0.671) remained unchanged. After adjustment for demographic characteristics, health behaviors, and metabolic factors, the post-pandemic period remained independently associated with RSP (odds ratio, 1.571; 95% confidence interval, 1.036–2.380; p = 0.033). Conclusions: The prevalence of RSP increased significantly after the COVID-19 pandemic and was accompanied by declines in lung volume-related pulmonary function without evidence of increased airflow obstruction. These findings highlight the importance of strategies targeting metabolic health, obesity, and physical function to preserve respiratory health in the post-pandemic era.